Bilirubin level 1 week after hepatoportoenterostomy predicts native liver survival in biliary atresia - Huang, Cho-Yi; Chang, Mei-Hwei; Chen, Huey-Ling; Ni, Yen-Hsuan; Hsu, Hong-Yuan; Wu, Jia-Feng (Pediatric research, 2020)
Background To determine a very early predictive biomarker after hepatoportoenterostomy (HPE) for the prediction of native liver survival in biliary atresia (BA) patients. Methods A retrospective chart review was conducted of BA patients in our hospital between August 2000 and April 2019. The serum total bilirubin (T-bil), direct bilirubin, and gamma-glutamyl transferase level 1 week after HPE were analyzed. The clinical outcome predictors were investigated. Results A total of 90 BA patients were recruited. Receiver operating characteristic curve analysis showed that a post-HPE 1-week T-bil level ≤4.85 mg/dL predicted jaundice-free after HPE ( P = 0.02). BA patients with a post-HPE 1-week T-bil ≤4.85 mg/dL were more likely to be jaundice-free within 3 months of HPE (odds ratio = 3.53; P = 0.006). Kaplan–Meier plot analysis showed that the likelihood of native liver survival and jaundice-free native liver survival were significantly higher in BA subjects with a post-HPE 1-week T-bil ≤4.85 mg/dL than in other subjects ( P = 0.01 and 0.01, respectively). Conclusions The serum post-HPE 1-week T-bil level may predict the long-term outcome in BA patients. A post-HPE 1-week T-bil ≤4.85 mg/dL correlated with better native liver survival and jaundice-free native liver survival in BA patients.